Dynamic Change of Cognitive Reserve: Associations with Changes in Brain, Cognition, and Diagnosis - Bettcher, Brianne M. (Neurobiol Aging, 2019)
Cognitive reserve is inherently a dynamic construct; however, traditional methods of estimating reserve have focused on static proxy variables. A recently proposed psychometric approach entails modeling reserve as residual cognition not explained by demographic and brain variables. In this study, we extended this approach to longitudinal measurement and examined how change in reserve relates to clinical outcomes in late life and influences the effect of brain atrophy on cognitive decline. Results indicated that cognitive reserve changes were associated with progression of clinical diagnosis. More rapid depletion of cognitive reserve was associated with faster decline in non-memory cognitive functions, even after accounting for longitudinal brain atrophy. The effect of longitudinal brain atrophy on cognitive decline differed based on the extent to which an individual’s reserve changed. Whereas depletion of reserve appeared to unmask the effects of brain atrophy on cognitive decline, maintenance of reserve buffered against the negative effects of brain atrophy. Study results highlight that changes in reserve may have important implications for individual differences in cognitive aging trajectories.